Spectral analysis of the four-wave mixing in a cold atomic sample using a single CW laser - ALMEIDA, Alexandre Andrade Cavalcanti de (2019)
We describe an experimental and theoretical study of the four-wave mixing spectrum in ⁸⁷Rb atoms trapped in a magneto-optical trap. Our experimental setup uses a single cw laser to produce two copropagating beams inducing two identical four-wave mixing processes. The initial goal of the work was to analyze and compare these two signals, looking for what information they could give about the atomic system. However, since a single spectrum presents an unexpected valley around the resonance, we will focus the analyses and theoretical modeling in explaining this feature. In order to explain the nature of this valley, we performed several series of measurements, changing parameters such as laser intensity or optical depth of the sample. To interpret the experimental results our theoretical model consists of a simple four-level N-shaped system. We write the Bloch equations and solve them considering the lowest order solution. Four excitation routes arise from this solution, but only the direct excitation route to the four-wave mixing process seems to agree partially with the experimental data. To improve the agreement, we add the absorption of the input beams and of the generated light. Therefore, our model gives evidence that the valley is due to a dispersion in a high intensity regime and to absorption effects for a low intensity regime. We discuss in further details the successes and failures of this model as well as a few options to achieve better descriptions.